2008
DOI: 10.1248/cpb.56.668
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Characterization of Emulsions Using .BETA.-Cyclodextrin as an Emulsifier

Abstract: The preparation and characterization of n-alkane/water emulsions using b b-cyclodextrin (b b-CD) were studied. The prepared n-alkane/water emulsions were of the oil-in-water (O/W) type, and the stability of emulsions was in the order of n-hexadecaneϾn-dodecaneϾn-octane. From observations using polarized light microscopy and powder X-ray diffraction measurement, it was suggested that the formation of a dense film at the oil-water interface and the three-dimensional structural network created by precipitated com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…In these studies, the mechanism of emulsion formation using CDs and the different emulsifying properties of the CDs were not sufficiently investigated. We have investigated the preparation of emulsions using CDs as the emulsifier [4][5][6][7] . In these works, it was suggested that a dense film at the oilwater interface and a three-dimensional structural network in the continuous phase formed by precipitated CD complexes are necessary for the formation of a stable emulsion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the mechanism of emulsion formation using CDs and the different emulsifying properties of the CDs were not sufficiently investigated. We have investigated the preparation of emulsions using CDs as the emulsifier [4][5][6][7] . In these works, it was suggested that a dense film at the oilwater interface and a three-dimensional structural network in the continuous phase formed by precipitated CD complexes are necessary for the formation of a stable emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…The n-alkane/water emulsions must be a type of Pickering emulsion because precipitate of CD-origin was adsorbed to the oil-water interface [4][5][6][7] . The formation of Pickering emulsions is known to be related to the contact angle (q ow ) that the solid particle forms with the interface 11,12) .…”
mentioning
confidence: 99%
“…Consequently, it was thought that the formed W/O emulsion is a kind of Pickering emulsion, similar to the O/W emulsion previously reported. 2,3) The type of Pickering emulsion is governed by the wettability of the solid particles at the oil-water interface 6,7) ; that is to say, a solid particle of q ow Ͻ90°stabilizes O/W emulsion, and that of q ow Ͼ90°stabilizes W/O emulsion, as shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…1) We have recently reported the preparation and formation mechanism of emulsions using natural CDs as an emulsifier. 2,3) In these studies, it was suggested that the formation of a dense film at the oil-water interface and a three-dimensional structural network in the continuous phase by precipitated complexes derived from CD are necessary for the formation of a stable emulsion. Consequently, we concluded that the formed emulsions are a kind of Pickering emulsion, which is stabilized by solid particles.…”
Section: Notesmentioning
confidence: 99%
“…1) b-CD in particular can include a wide range of guest molecules, so b-CD has widely been utilized in formulations for medicines and food. 2,3) p-Dimethylaminobenzonitrile (DMABN) is known as a model probe for determining the mechanisms of inclusion in a solution. 4) DMABN molecules have been reported to adopt two different conformation, planar and twisted, in a solution.…”
mentioning
confidence: 99%